Peramalan Jumlah Produksi Daging Sapi Provinsi Sumatera Barat Menggunakan Metode Pemulusan Eksponensial Ganda Tipe Holt - Septri Novita; Arnellis Arnellis (Journal of Mathematics UNP, 2020)
Abstract — Beef is one of the sources of animal protein that is able to fulfill human nutritional needs. Beef production in West Sumatera Province comes from slaughterhouses, modern or traditional abattoirs. The purpose of this study is make a forecasting model for the amount of beef production in the province of West Sumatera that using the Holt type double exponential smoothing method and predict the amount of beef production based on the model that formed. Data takes from the data of beef production’s amount in the province of West Sumatera from 2005 until 2018 obtained from the Department of Animal Husbandry and Animal Health of West Sumatera’s Province. The method used is the method of Holt Type Double Exponential Smoothing, parameter α and ɣ minimize MSE is 0,9 and 0,1. The result of the forecast beef production in the province of West Sumatera from 2019 until 2023 in a row is 20.644,40 ton, 20.892,66 ton, 21.140,93 ton, 21.389,19 ton, dan 21637,45 ton. Keywords — Forecasting, Double Eksponential Smoothing Type Holt, Beef Production.